SOCIAL INVESTMENT: CSR STRATEGY IN THE FIELD OF COMMUNITY DEVELOPMENT BY PT. PLN INDONESIA POWER CILEGON PGU - Cantika, Shofa Alya; Siregar, Herlina; Fikri, Ali Nur (Media Mahardhika, 2024)
When industrialization began in 1930, in line with the world economic recession, there were massive protests from the public demanding company transparency in their operational activities. The term Corporate Social Responsibility or CSR emerged among companies, which was soon followed by legal authority that regulated mandatory CSR for companies and in the 2000s in Indonesia, the term CSR began to be known intensively in social investment through the concept of development. public. The approach used in this research is qualitative with descriptive methods. Through observations and interviews conducted, the research results showed that the social investment carried out by PT. PLN Indonesia Power inventories the community around the company with social service activities, environmental service and other assistance activities through community service and community relations programs and empowers them in various aspects through several programs, such as plasma farmers, Climate Villages, Waste Banks and MSMEs. These three programs are interrelated in maintaining harmony and public trust. So that through these programs, sustainability can be achieved for the company. Key words: social investment, community development, CSR